MEDIA ULAR TANGGA TIPE SOAL HOTS ( Higher Order Thinking Skill) UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK - Isnawati, Beti Aprilia; Muhfahroyin, Muhfahroyin; Sujarwanta, Agus (Universitas Muhammadiyah Metro, 2022)
media is a tool used to convey messages or information. Learning media are developed because of the difficulties often experienced by students in the learning process. Difficulties that are often experienced by students do not understand the material presented so that students' activities are low, students are less active and less motivated to learn, so the learning outcomes of students do not reach the specified KKM value. The purpose of this study is to produce a ladder snake learning media that uses HOTS type questions that are valid and appropriate to be used to overcome problems experienced by students. This type of research uses a 4-D model that has 4 stages, namely, defining the design, development and dissemination. Research carried out until the development stage.